On the migration from enterprise management to integrated service level management. - Lundy, L. (IEEE Network : the magazine of global information exchange)
Enterprise management is concerned with the integrated management of enterprise-wide applications with underlying network and systems management. Service level management (SLM) provides a mechanism for linking business requirements with the specification of integrated management systems. SLM is popular in industry, although the meaning of "service" varies depending on to whom one is talking. Sometimes a service is understood with respect to networking elements alone (e.g., router throughput), sometimes in terms of application performance (e.g., packet latency), and sometimes in terms of user perception (e.g., URL response time). In this article we provide a multi-agent framework for integrated SLM that subsumes these different approaches into a single comprehensive top-down management system from a high-level business perspective. This multi-agent-based system is illustrated with a case study of a typical enterprise in the United States, showing how enterprise management is migrating to the concept of service management